2016
DOI: 10.1038/srep35196
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin sensitizes human esophageal cancer to TRAIL-induced apoptosis via AMPK activation

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising anticancer agent for esophageal squamous cell carcinoma (ESCC). Forced expression of CHOP, one of the key downstream transcription factors during endoplasmic reticulum (ER) stress, upregulates the death receptor 5 (DR5) levels and promotes oxidative stress and cell death. In this study, we show that ER stress mediated by thapsigargin promoted CHOP and DR5 synthesis thus sensitizing TRAIL treatment, which induced ESCC cells apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 73 publications
(91 reference statements)
3
30
0
Order By: Relevance
“…Interestingly, we found that the combination of lopinavir and ritonavir triggered TRAIL-receptor-mediated cytotoxicity and apoptosis by increasing the expression of the TRAIL receptor DR5. Several studies have shown that ER stress induction increased the expression of TRAIL receptors, thereby sensitizing cancer cells to TRAIL and inducing TRAIL-mediated apoptosis (11,14,38). Compatible with those studies, the increased DR5 expression we found was shown to be due to ER stress induced by the combination.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, we found that the combination of lopinavir and ritonavir triggered TRAIL-receptor-mediated cytotoxicity and apoptosis by increasing the expression of the TRAIL receptor DR5. Several studies have shown that ER stress induction increased the expression of TRAIL receptors, thereby sensitizing cancer cells to TRAIL and inducing TRAIL-mediated apoptosis (11,14,38). Compatible with those studies, the increased DR5 expression we found was shown to be due to ER stress induced by the combination.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies demonstrated that ER stress induced AMPK expression in malignancies (11,12). Furthermore, AMPK is known to act against cancer by suppressing the mTOR pathway (13).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, suppression of eIF2α dephosphorylation by the salubrinal (ER stress inhibitor; a specific eIF2α phosphorylation-inducing agent) improves the TRAIL-induced apoptosis in human hepatoma HepG2 cells [ 127 ]. The ER stress inducer thapsigargin sensitizes human esophageal cancer EC109 and TE12 cells to TRAIL-induced apoptosis via AMPK activation [ 128 ]. Accordingly, the role of ER stress in TRAIL-induced apoptosis remains controversial and may depend on tissue-specific or TRAIL resistant characters.…”
Section: Interactions Between Trail Wnt Shh Tgfβ and Mirna Sigmentioning
confidence: 99%
“…In our study, we explored the actions of ERS in the anti-NSCLC activities of PT. ER is the main storage site of Ca 2+ , and any disruption in its accumulation can promote ER stress 23 , 33 . Our study found PT treatment could immediately disturb the Ca 2+ homeostasis in ER and cytoplasm, and significantly upregulate cytosolic Ca 2+ levels in PC9 cells.…”
Section: Discussionmentioning
confidence: 99%